The RNA polymerase II CTD kinase Ctk1 functions in translation elongation - Röther, Susanne (Cold Spring Harbor Laboratory Press, 2007)
Translation is a highly complex process that is regulated by a multitude of factors. Here, we show that the conserved kinase Ctk1 functions in translation by enhancing decoding fidelity. Ctk1 associates with translating ribosomes in vivo and is needed for efficient translation. Ctk1 phosphorylates Rps2, a protein of the small ribosomal subunit, on Ser 238. Importantly, Ctk1-depleted as well as rps2-S238A mutant cells show a defect in translation elongation through an increase in the frequency of miscoding. The role of Ctk1 in translation may be conserved as the mammalian homolog of Ctk1, CDK9, also associates with polysomes. Since Ctk1 interacts with the TREX (transcription and mRNA export) complex, which couples transcription to mRNA export, Ctk1/CDK9 might bind to correctly processed mRNPs during transcription and accompany the mRNP to the ribosomes in the cytoplasm, where Ctk1 enhances efficient and accurate translation of the mRNA.